Obtenção de novos derivados de ß-naftol e cardanol hidrogenado e avaliação dos seus efeitos antioxidativos em gasolina automotiva - Dantas, Michelle Sinara Gregório (2005)
The chemical nature of the hidrocarbons found in gasoline directly affects the formation of oxidation complexes known as gums. Such complexes are slightly soluble in gasoline and their formation is delayed with the use of inhibitors, known as antioxidants. In this study, a synthetic compound (βnaphtol) and a natural subproduct (hydrogenated cardanol, derived from cashewnut shell liquid CNSL) have been used in order to generate novel antioxidant substances. These compounds were submitted to chemical reactions including alkylation, nitration and reduction, with the purpose of forming the following derivatives: 6(Nethyl,Nethylamino)βnaphtol (AO1); 6(Nethyl,Ndiethylamino)βnaphtol (AO2); aminoβnaphtol (AO3); 2(Nethyl,Nethylamino)pentadecylphenol (AOC1), 2(Nethyl,Ndiethylamino)pentadecylphenol (AOC2) and aminopentadecylphenol (AOC3). The derivatives were subjected to accelerated oxidative stability assays (Potential Gum and Induction Period) and to storage assays (Washed Gum and ASTM Color) during six months, with naphtha provided by the petroleum refinery RPBC (Refinaria Presidente Bernardes de Cubatão, in Brazil). The results for the derivatives were compared to those for commercial additives [DBPC (2,6ditbutyl4methylpcresol) and PDA (N,N disecbutylpphenylenediamine)], which were also added to the naphtha produced at RPBC at the moment of sampling. From all tested antioxidants, the novel antioxidant AOC1 (derived from hydrogenated cardanol) yielded a better global performance. During the period of time in which the naphtha was stored, an examination of this material was carried out in parallel, using the mass spectrometry technique. This study allowed to monitor the formation of a triolefinic compound, as well as the observation of subsequent formation and rupture of the olefinic constituents. As an eventual result from these experimental investigations, a reaction route leading to gum formation has been suggested